Internet, phone, mail and mixed-mode surveys the tailored design method - Vidal DÍAZ DE RADA, Vidal (Revista Española de Investigaciones Sociológicas, 2024)
Internet, phone, mail and mixed-mode surveys: the tailored design method A. Dillman, Jolene D. Smyth, Leah Melani Christian John Wiley and Sons, 2014